HUBUNGAN PERILAKU SEDENTARY TERHADAP INDEKS MASSA TUBUH DAN LINGKAR PINGGANG PADA MAHASISWA PROGRAM STUDI SARJANA KEDOKTERAN UNIVERSITAS UDAYANA ANGKATAN 2019-2020 - Sugandhi, Adhe; Ayu Widianti, I Gusti; Muliani, Muliani; Yuliana, Yuliana (E-Jurnal Medika Udayana, 2022)
Sedentary behavior is the behavior of individuals who do less movement and use little energy. This has become a problem in the world and Indonesia in this era of accelerating globalization. Especially for medical students, the academic demands of students make this behavior often occur among students. Medical students are required to have good academic grades to perform complex tasks making this behavior unavoidable. The purpose of this study was to determine the relationship of sedentary behavior to body mass index and waist circumference in students of the undergraduate study program of medicine and medical professionals, Faculty of Medicine, Udayana University class of 2019-2020. This research was conducted using an analytical observational method with a cross sectional approach. The number of samples in this study amounted to 93 students with a sampling technique that is simple random sampling. Sedentary behavior, body mass index, and waist circumference were measured using a questionnaire based on the respondents' memories that were distributed online. The results of the chi-square analysis showed a significant value between sedentary behavior and body mass index (p=0.013), but not with sedentary behavior and waist circumference (p=0.553). The results of this study are expected that students can reduce sedentary behavior and increase physical activity in order to avoid a bad body mass index status.